Molecular interplays of the Entamoeba histolytica endosomal sorting complexes required for transport during phagocytosis - Bañuelos, Cecilia; Betanzos, Abigail; Javier-Reyna, Rosario; Galindo, Ausencio; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2022)
Entamoeba histolytica, the causative agent of human amoebiasis, exhibits a continuous membrane remodelling to exert its virulence properties. During this dynamic process, the Endosomal Sorting Complexes Required for Transport (ESCRT) machinery is a key player, particularly in phagocytosis, a virulence hallmark of this parasite. In addition to ESCRT, other molecules contribute to membrane remodelling, including the EhADH adhesin, EhRabs, actin, and the lysobisphosphatidic acid (LBPA). The endocytosis of a prey or molecules induces membrane invaginations, resulting in endosome and multivesicular bodies (MVBs) formation for cargo delivery into lysosomes. Alternatively, some proteins are recycled or secreted. Most of these pathways have been broadly characterized in other biological systems, but poorly described in protozoan parasites. Here, we encompass 10 years of ESCRT research in E. histolytica, highlighting the role of the ESCRT-I and ESCRT-III components and the EhADH and EhVps4-ATPase accessory proteins during phagocytosis. In particular, EhADH exhibits a multifunctional role along the endocytic pathway, from cargo recognition to endosome maturation and lysosomal degradation. Interestingly, the interaction of EhADH with EhVps32 seems to shape a concurrent route to the conventional one for MVBs biogenesis, that could optimize their formation. Furthermore, this adhesin is secreted, but its role in this event remains under study. Other components from the endosomal pathway, such as EhVps23 and LBPA, are also secreted. A proteomic approach performed here, using an anti-LBPA antibody, revealed that some proteins related to membrane trafficking, cellular transport, cytoskeleton dynamics, and transcriptional and translational functions are secreted and associated to LBPA. Altogether, the accumulated knowledge around the ESCRT machinery in E. histolytica, points it out as a dynamic platform facilitating the interaction of molecules participating in different cellular events. Seen as an integrated system, ESCRTs lead to a better understanding of E. histolytica phagocytosis.